SYNTHESIS OF BIOLOGICAL ACTIVE THIAZOLO-QUINAZOLINES - Veerappan Jeyachandran (International Journal of Modern Agriculture, 2020)
Thiazolo-quinazolinones are classes of fused heterocycles that are of considerable interest because of the diverse range of their biological properties 1. Many substituted quinazoline and quinazolinone derivatives possess a wide range of bioactivities such as antimalarial, anticancer, antimicrobial, antifungal, antiviral, antiprotozoan, anti-inflammatory, diuretic, muscle relaxant, antitubercular, antidepressant, anticonvulsant, acaricidal, weedicide, and many other biological activities. Quinazoline and quinazolinone compounds are also used in preparation of various functional materials for synthetic chemistry and also present in various drugs molecules (Figure 1). This review is an attempt to expand the huge potentiality and focused on the various biological activities of quinazolines and quinazolinones 2.